IMI2-PainCare-BioPain-RCT2 protocol: a randomized, double-blind, placebo-controlled, crossover, multicenter trial in healthy subjects to investigate the effects of lacosamide, pregabalin, and tapentadol on biomarkers of pain processing observed by non-invasive neurophysiological measurements of human spinal cord and brainstem activity - Leone, Caterina; Di Stefano, Giulia; Di Pietro, Giuseppe; Bloms-Funke, Petra; Boesl, Irmgard; Caspani, Ombretta; Chapman, Sonya C.; Finnerup, Nanna Brix; Garcia-Larrea, Luis; Li, Tom; Goetz, Marcus; Mouraux, André; et al. (Current controlled trials in cardiovascular medicine, 2022)
Background IMI2-PainCare-BioPain-RCT2 is one of four similarly designed clinical studies aiming at profiling a set of functional biomarkers of drug effects on specific compartments of the nociceptive system that could serve to accelerate the future development of analgesics. IMI2-PainCare-BioPain-RCT2 will focus on human spinal cord and brainstem activity using biomarkers derived from non-invasive neurophysiological measurements. Methods This is a multisite, single-dose, double-blind, randomized, placebo-controlled, 4-period, 4-way crossover, pharmacodynamic (PD) and pharmacokinetic (PK) study in healthy subjects. Neurophysiological biomarkers of spinal and brainstem activity (the RIII flexion reflex, the N13 component of somatosensory evoked potentials (SEP) and the R2 component of the blink reflex) will be recorded before and at three distinct time points after administration of three medications known to act on the nociceptive system (lacosamide, pregabalin, tapentadol), and placebo, given as a single oral dose in separate study periods. Medication effects on neurophysiological measures will be assessed in a clinically relevant hyperalgesic condition (high-frequency electrical stimulation of the skin), and in a non-sensitized normal condition. Patient-reported outcome measures (pain ratings and predictive psychological traits) will also be collected; and blood samples will be taken for pharmacokinetic modelling. A sequentially rejective multiple testing approach will be used with overall alpha error of the primary analysis split between the two primary endpoints, namely the percentage amplitude changes of the RIII area and N13 amplitude under tapentadol. Remaining treatment arm effects on RIII, N13 and R2 recovery cycle are key secondary confirmatory analyses. Complex statistical analyses and PK-PD modelling are exploratory. Discussion The RIII component of the flexion reflex is a pure nociceptive spinal reflex widely used for investigating pain processing at the spinal level. It is sensitive to different experimental pain models and to the antinociceptive activity of drugs. The N13 is mediated by large myelinated non-nociceptive fibers and reflects segmental postsynaptic response of wide dynamic range dorsal horn neurons at the level of cervical spinal cord, and it could be therefore sensitive to the action of drugs specifically targeting the dorsal horn. The R2 reflex is mediated by large myelinated non-nociceptive fibers, its circuit consists of a polysynaptic chain lying in the reticular formation of the pons and medulla. The recovery cycle of R2 is widely used for assessing brainstem excitability. For these reasons, IMI2-PainCare-BioPain-RCT2 hypothesizes that spinal and brainstem neurophysiological measures can serve as biomarkers of target engagement of analgesic drugs for future Phase 1 clinical trials. Phase 2 and 3 clinical trials could also benefit from these tools for patient stratification. Trial registration This trial was registered on 02 February 2019 in EudraCT (2019-000755-14). Keywords: Pain, Analgesics, PK/PD, Spinal cord, Biomarkers, RIII flexion reflex, N13 somatosensory evoked potentials, Hyperalgesia, RCT, Healthy subjects